Grasses of the Upper Gangetic Plain and some Aspects of their Ecology - Raizada, M. B. (Indian Forester, 1954)
This work deals with the grasses of 'The Upper Gangetic Plain', covering an area of approximately 196,000 square miles, namely the states of Uttar Pradesh, Delhi, Ajmer-Merwara, East Rajasthan, Vindhya Pradesh and Madhya Bharat (Places above 2,300 ft. have been excluded ). After discussing some aspects of ecology and the evolution of the grasses, forest and grassland climates, indicator value of grasses, grazing problems and improvement of fodder supplies, two hundred and fifty species belonging to about one hundred genera found in the area have been enumerated. Since considerable nomenclatural confusion exists in the Gramineae, efforts have been made to follow the rules of nomenclature and to adopt the most recent names as far as practicable. Three new names, viz., Erianthus procerum (Roxb.) Raizada, Themeda longispatha ( Hack. ) Raizada et Jain and Cymbopogon stracheyi (Hk. f.) Raizada et Jain have been proposed. The present work is based chiefly on the material deposited in the Dehra Dun Herbarium and is the first consolidated account of the Gramineae of 'The Upper Gangetic Plain, and of the adjacent Siwalik and the Sub-Himalayan tracts'.